SYNTHESIS AND CHARACTERIZATION OF GRAPHENE FROM COCONUT FIBER (COCOS NUCIFERA) AS ANODE MATERIALS FOR LI-ION BATTERY - Indra Gunawan; Wagiyo H; Bambang Sugeng; Sudaryanto Sudaryanto (Jurnal Sains Materi Indonesia, 2019)
Synthesis of graphene from coconut fiber conducted in two stages. The first stage is heating the powder of coconut fiber that passes 325 meshes by hydrothermal method at 200o C for 4 hours. Furthermore, the pyrolysis then treated at temperature of 1000° C for 2 hours. The grain size and surface morphology from graphene observed using SEM in the 1000X magnification. From the SEM image of graphene, it shows the pattern of several thick layers build mutual three-dimensional, forming a flake structure. Observations also show stacks of graphene structure with more big flakes forming a thick pallet. Another characterization was performed by using X-ray diffractometer (XRD), Raman Spectrometer and LCR meter. From XRD observation there is an amorphous pattern at the first stage of synthesis, after pyrolysis at 1000o C for 2 hour a peak near 2θ = 24o, 42oand 52o which corresponds to crystal indexes (002), (400) and (511) became visible. The peak at around 1350 cm-1 in the Raman is the D band. The D band is represented defects, like disruption in the sp2 bonding because of heptagon and pentagon rings, vacancies, edge effect, and etc. DC conductivity or bulk electrical conductivity of about 4.6 x 10-3 Scm-1.